Pengaruh Intellectual Capital, Perencanaan Pajak, Dan Pengungkapan Enterprise Risk Management Terhadap Nilai Perusahaan - Riani Fadilah; Mayar Afriyenti (Universitas Negeri Padang, 2020)
The aim of this study was to analyze the influence of intellectual capital, tax planning, enterprise risk management discloure on firm value. The data used in this study are annual reports In manufacturing companies listed on the indonesia stock exchange (idx) in the period 2014-2018. The method of taking data samples using purposive sampling method based on certain criteria. Based on the retrieval method obtained A sample of 162 companies. Hypothesis testing in this study uses multiple linear regression analysis. The results show that structural capital, tax planning, and enterprise risk management discloure has no influence on firm value and human capital also customer capital have a positive influence on firm value. The results of this study contribute to the development of knowledge related to company value, especially the importance of human capital and customer capital. For practice, this research provides input to companies in order to maximize their human capital and customer capital. Keywords: Intellectual Capital; Tax Planning; Enterprise Risk Management Disclosure; Firm Value